Effect of heater wire configuration and nanotexturing on force generated by self-propelled bubble-driven propeller. (March 2022) - Kim, Yong Il; Bang, Boo-Hyoung; Jang, Keunhee; An, Seongpil; Yarin, Alexander L.; Yoon, Sam S.
Highlights: The direction and magnitude of the bubble-driven force per varying heater wire installations are investigated. The wire heater installed at both surfaces of the heater yielded the strongest self-propelled motion. A two- to four-fold increase in the propelling force was detected for the nanotextured wire cases, compared to those in the non-textured cases. Abstract: The heat generated on a heater submerged in a liquid reservoir is transported away by rising bubbles during pool boiling under buoyancy conditions. This bubble-driven heat transport cools the heater surface, and as a result, the critical heat flux (CHF) is delayed, or even avoided. At detachment from the heated surface, bubbles undergo necking owing to the interplay between evaporation, buoyancy, vapor recoil, and surface tension. The surface tension tends to hold a bubble at the heater surface, whereas the buoyancy force pulls it apart. On the other hand, vapor recoil pushes the heater downwards. Eventually, in many cases the buoyancy force prevails because of the evaporation-driven volume growth of the bubbles, and their detachment. Here, we observe that during bubble detachment, the heater is propelled in the direction of the rising bubbles. This self-propelled motion can be used to shed bubbles, which enhances the pool boiling performance. In this work, we study the heater shaped as a 'wavy' wire and demonstrate the extent to which the bubble-driven force and its direction and magnitude depend on a particular way of the in-plane wavy heater wire installation. The heating wire was installed at the upper (top) or lower (bottom) surfaces of a plate and also, two wire heaters were installed at both surfaces of the plate, and the supplied heat was maintained at a constant level. It was found that the case where the wire heater installed at both surfaces of the plane heater yielded the strongest self-propelled motion. In an additional investigation, the heating wire was nanotextured with nickel nanocones electroplated on its surface. The nanotextured heater surface increased the number of bubble nucleation sites and thus magnified the corresponding force for all the heater wire installations, compared to those in the non-textured cases.